Britain’s Indo-Pacific Security and Trade Policies: Continuity and Change Under the Labour Government - Samir PURI (East Asian Policy)
The United Kingdom’s main motivation for its engagement in the Indo-Pacific is commercial, alongside its contributions to regional security. In July 2024, a Labour government replaced the Conservative government. While the United Kingdom’s commitment to the Indo-Pacific is expected to remain steadfast, managing the ongoing war in Europe and the expected impact of the incoming Trump presidency on transatlantic relations will challenge Labour for years to come. The United Kingdom’s long-term interests in the Indo-Pacific must now be managed alongside these more pressing concerns.